Single-Step Gene Knockout of the SUC2 Gene in Saccharomyces cerevisiae : A Laboratory Exercise for Undergraduate Students - Jurre Hageman (American Society for Microbiology, 2018)
This article describes a relatively straightforward procedure to knock out the gene that encodes the invertase enzyme in baker’s yeast. The SUC2 gene, which encodes for the invertase enzyme, is knocked out by a single-step PCR knock out method. The knockout is subsequently confirmed at the genetic level by PCR and agarose gel electrophoresis. The knockout is confirmed at the biochemical level by measuring the activity of the invertase enzyme using a colorimetric assay. This tips and tools article describes an easily scalable, inexpensive, yet challenging research project helping undergraduate students at the Bachelor level to conceptualize the effect of the deletion of a gene encoding an enzyme.